Study of surface roughness during droplet impact on a heated aluminium - Teevagar Gabrial Nayagam A/L Arulappan (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The main objective of this project is to study the surface roughness of material at different surface temperature and relationship between temperatures at high and low temperature. This experiment utilized Aluminium and the material will place on the hot plate. The droplet of the water will be release from the dropper at the material when heated to three different temperature 100C, 200C and 300C. The experiment was done to investigate the droplet impact of the microstructure condition of the surface roughness of the material when liquid-solid contact at three different surface temperatures which is 100, 200 and 300 C.